Preclinical studies of the falnidamol as a highly potent and specific active ABCB1 transporter inhibitor - Baojie Liu; Yongzheng Lu; Ruihui Lin; Junbao Xu; Zilin Shang; Xinyu Hou; Xulong Shao; Zhifang Pan; Tao Yu; Weiguo Feng (BMC Cancer)
Abstract Background ABCB1 overexpression is a key factor in causing multidrug resistance (MDR). As a result, it is crucial to discover effective medications against ABCB1 to overcome MDR. Falnidamol, a tyrosine kinase inhibitor (TKI) targeting the epidermal growth factor receptor (EGFR), is currently in phase 1 clinical trials for the treatment of solid tumors. In this work, we assessed whether falnidamol could act as an inhibitor of ABCB1 to reverse ABCB1-mediated MDR. Methods The reversal effect of falnidamol on MDR was assessed by MTT, colony formation, 3D microsphere, and xenograft model assays. The protein expression or cellular localization was tested by western blot and immunofluorescence analysis. The intracellular doxorubicin accumulation and efflux were assessed by flow cytometry. The ATPase activity of ABCB1 was detected by a microplate reader. The interaction between falnidamol and ABCB1 was evaluated by docking analysis and cellular thermal shift assay. Results Our data showed that falnidamol specifically reversed ABCB1-mediated MDR but not ABCG2-mediated MDR in vitro and in vivo. Mechanistic studies suggested falnidamol had no effect on ABCB1 expression or cellular localization, nor on the AKT or ERK pathways. Further studies found that falnidamol reduced ABCB1’s efflux function, resulting in enhanced intracellular agent accumulation and thus overcoming MDR. ATPase assay showed that falnidamol suppressed the ABCB1 ATPase activity. Furthermore, docking analysis and cellular thermal shift assay indicated that falnidamol bound directly to the drug-binding site of ABCB1 transporter. Conclusion The present study proves that falnidamol acts as a highly potent and specific active ABCB1 transporter inhibitor, and can reverse ABCB1-mediated MDR, implying that combining falnidamol with ABCB1 substrate chemotherapeutic agents has the potential to overcome ABCB1-mediated MDR.